Leaching and residual effects of oxadiazon as a function of the movement of water depth application and incorporation of soil organic matter - Mendes, Kassio Ferreira; dos Reis, Marcelo Rodrigues; de Matos, Ana Karollyna Alves [UNESP]; Inoue, Miriam Hiroko; Dias, Roque de Carvalho; Ronchi, Cláudio Pagotto (My University, 2014)
Knowledge of soil and herbicide interactions is of fundamental importance for minimizing negative environmental consequences, especially to water resources, and to increase weedy plant control efficiency. The objective of this work was to evaluate the leaching and residual effects of oxadiazon applied to pre-emergent plants by means of a bioassay as a function of the time of water depth application and soil organic matter. Using a randomized block design, the treatments were arranged in a scheme of subdivided parcels 4 × 2 × 4 + 1, with four repetitions. The experimental parcels were composed of the application time of the water depth (0; 10 mm before; 10 mm afterward; and 10 mm before and after the oxadiazon application), beyond the control (0 mm and 0 g ha-1 of oxadiazon). The subparcels that with or without soil organic matter incorporated (8 t ha-1) were evaluated, as were the subsubparcels of the soil depths (0.00 - 0.05, 0.05 - 0.10, 0.10 - 0.15 and 0.15 - 0.20 m). To determine oxadiazon leaching (1, 000 g ha-1), soil samples were collected 0, 30, 60 and 90 days after application (DAA) of oxadiazon, and the residual effect was determined at 0, 15, 30, 45, 60, 75, 90 and 105 DAA. At 0 DAA, the leaching was greater with a sequential application of the water depth at 10/10 mm, reaching a depth of 0.15 - 0.20 m. The greatest half-life (t1/2) of oxadiazon was 54 days at the 0.00 - 0.05 m depth with the application 10 mm before and after the oxadiazon application. Results showed that the application time of the water depth interfered with the leaching and residual effect of oxadiazon in the soil, and may interfere with herbicide efficiency in controlling weedy plants and reaching the deepest soil depths. The incorporation of 8 t ha-1 of soil organic matter did not have any effect on these processes.
Keywords: Bioindicator; Efficiency of control; Mobility; Persistence of herbicide